ECTHR_CHAMBER 29953/08 vom 22. September 2011 , AFFAIRE A.S.P.A.S. ET LASGREZAS c. FRANCE - Ecthr Chamber (2011)
Non-violation de P1-1;Non-violation de l'art. 11;Partiellement irrecevable; No violation: 11